Koperasi Wanita Dan Pemberdayaan Perempuan Dalam Menumbuhkan Ekonomi Kerakyatan di Kota Malang - Hatneny, Aleria Irma (JU-ke: Jurnal Ketahanan Pangan, 2017)
SMEs and cooperative which is a reflection of the form of a populist economy experienced tidal dynamics. There is also a pessimistic view that the cooperative as a pillar of the national economy increasingly become limited jargon. The accumulation of wealth and economic power in some business entities becomes a challenge for SMEs and Cooperatives in general whether able to compete against private domination. Cooperative is one of the economic actors in addition to state-owned and private, although the contribution of cooperatives to GDP is still relatively small compared to the contribution of state-owned and private. Large number of cooperatives can not be considered one perspective because it holds great potential if managed optimally. In East Java, especially in the city of Malang, Cooperatives activities especially Women cooperative holds potency of power to regional economy. Women have distinctive characteristics and are able to play a role in managing the household and developing a family economy. This qualitative research which aims to describe and identify the implementation of womens cooperative programs by the Government and its implications on the empowerment of women and the populist economy in Malang. Processed data is primary data and secondary data. Data collection methods used were interviews of key informants, documentation and field observation. From the result of research and discussion, it can be concluded that there is a key role of womens cooperative management in Malang to the successful implementation of Government programs in the empowerment of its members, especially in developing the peoples economy